1997
DOI: 10.1016/s0925-5710(96)00554-3
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Serum soluble interleukin-2 receptor (sIL-2R) levels were determined in patients with chronic myeloproliferative disorders (CMPD): 18 with chronic myelogenous leukemia in chronic phase (CML in CP), seven with CML in accelerated phase (AP) or blastic crisis (BC), six with polycythemia vera (PV), eight with essential thrombocythemia (ET), one with primary myelofibrosis (PMF), and 50 controls. The mean (+/-S.E.M.) levels were higher in CMPD than in controls (CML in AP or BC, 2693 +/- 694 U/ml, P < 0.0001; CML in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…Several studies have shown that patients in advanced stages of disease have higher levels of sCD25 in plasma compared to patients in less advance stages and that sCD25 can be a prognostic factor for patients with lymphoma [47], [49], [50], [51], [52]. In CML, patients in accelerated phase and blast crisis have higher levels of sCD25 in plasma [47], [50]. In the present paper we show that the level of sCD25 in plasma is higher in HR patients.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Several studies have shown that patients in advanced stages of disease have higher levels of sCD25 in plasma compared to patients in less advance stages and that sCD25 can be a prognostic factor for patients with lymphoma [47], [49], [50], [51], [52]. In CML, patients in accelerated phase and blast crisis have higher levels of sCD25 in plasma [47], [50]. In the present paper we show that the level of sCD25 in plasma is higher in HR patients.…”
Section: Discussionsupporting
confidence: 59%
“…We as well as others have shown that patients with hematological malignancies, such as B cell malignancies and CML, have increased level of sCD25 in plasma [21], [23], [47], [48]. Several studies have shown that patients in advanced stages of disease have higher levels of sCD25 in plasma compared to patients in less advance stages and that sCD25 can be a prognostic factor for patients with lymphoma [47], [49], [50], [51], [52]. In CML, patients in accelerated phase and blast crisis have higher levels of sCD25 in plasma [47], [50].…”
Section: Discussionmentioning
confidence: 98%
“…The first experimental data that showed elevations of serum and/or plasma cytokines in Ph− MPN date back to more than 15 years. In the 90s, changes in serum levels of interleukin (IL) such as IL6 [ 5 , 6 ], IL2 and its soluble receptor [ 7 ], and of tumor necrosis factor (TNF α ) [ 8 ] were already reported associated with disturbances of blood cell counts. The study of Hermouet et al [ 9 ] in 2002 has expanded this panel, showing elevated serum levels of IL8 and IL11 in patients with PV, compared to healthy subjects.…”
Section: Cytokine Network In Myeloproliferative Neoplasmsmentioning
confidence: 99%
“…Patients with primary myelofibrosis (PMF) have been shown to share both clinical symptoms and laboratory abnormalities with patients with systemic inflammatory response syndrome, such as elevation in the erythrocyte sedimentation rate, Creactive protein (CRP), IL-1b, IL-6, IL-8, and TNF (54). High plasma levels of IL-6 and IL-8 were found to be significantly associated with severity of constitutional symptoms in PMF patients by Tefferi et al (43) Elevations of IL-2, and sIL-2R, Il-6, IL-8, and b2-microglobulin, have been associated with blast transformation of CML or Ph-MPNs, based on several studies (43,50,51,55). IL-8, also known as CXCL8, is a CXC family cytokine found to be expressed by HSPC in MF (48) and de novo AML (56) patients.…”
Section: Cytokines Are Elevated In All Chronic Phase Mpns In Comparison With Healthy Aged Individualsmentioning
confidence: 99%